Psychological Impact of Gadget Users: Dampak Psikologis Pengguna Gadget - Purnomo, Yuli Endah Ferawaty; Azizah, Nurul (Wadah Inovasi Indonesia, 2025)
adolescence is a transition period from childhood to adulthood, marked by significant physical, psychological, cultural, and psychosocial changes. This research investigates the impact of gadget addiction on a sixth-grade child (S) who uses gadgets for more than 2 hours daily. The study found that while gadgets can positively facilitate learning and communication with peers, they negatively affect psychological development, particularly emotional growth and moral development. Children using gadgets excessively become irritable and display reduced discipline, often neglecting studies in favor of watching TikTok and YouTube. The study highlights the critical role of parents in mitigating these negative effects by engaging children in activities aligned with their interests, thereby effectively reducing gadget usage.